Combining classical and molecular approaches elaborates on the complexity of mechanisms underpinning anterior regeneration - Evans, Deborah J.; Owlarn, Suthira; Romero, Belan Tejada; Chen, Chen; Aboobaker, A. Aziz (Public Library of Science, 2011)
The current model of planarian anterior regeneration evokes the establishment of low levels of Wnt signalling at anterior wounds, promoting anterior polarity and subsequent elaboration of anterior fate through the action of the TALE class homeodomain PREP. The classical observation that decapitations positioned anteriorly will regenerate heads more rapidly than posteriorly positioned decapitations was among the first to lead to the proposal of gradients along an anteroposterior (AP) axis in a developmental context. An explicit understanding of this phenomenon is not included in the current model of anterior regeneration. This raises the question what the underlying molecular and cellular basis of this temporal gradient is, whether it can be explained by current models and whether understanding the gradient will shed light on regenerative events. Differences in anterior regeneration rate are established very early after amputation and this gradient is dependent on the activity of Hedgehog (Hh) signalling. Animals induced to produce two tails by either Smed-APC-1(RNAi) or Smed-ptc(RNAi) lose anterior fate but form previously described ectopic anterior brain structures. Later these animals form peri-pharyngeal brain structures, which in Smed-ptc(RNAi) grow out of the body establishing a new A/P axis. Combining double amputation and hydroxyurea treatment with RNAi experiments indicates that early ectopic brain structures are formed by uncommitted stem cells that have progressed through S-phase of the cell cycle at the time of amputation. Our results elaborate on the current simplistic model of both AP axis and brain regeneration. We find evidence of a gradient of hedgehog signalling that promotes posterior fate and temporarily inhibits anterior regeneration. Our data supports a model for anterior brain regeneration with distinct early and later phases of regeneration. Together these insights start to delineate the interplay between discrete existing, new, and then later homeostatic signals in AP axis regeneration.